“Evil women” in the Paintings by “De Zotte Schilders”: Iconographical and Social Aspects - Kovbasiuk, Stefania A. (Actual Problems of Theory and History of Art, 2013)
The iconography of the images of the “evil women”, their social and ideological background in the Netherlandish art of the first half of the 16th c. in the painting of so-called “De Zotte Schilders” — “the comic painters” are analyzed in this paper. Using visual and the literary sources the author identifies three main images of the “evil women”: the wicked wife, the procuress and the “old witch”, each of them has its own particular iconography.
Keywords: “De Zotte Schilders”; the Northern Renaissance; gender history; grotesque